IMPROVING STUDENTS’S READING COMPREHENSION ON DESCRIPTIVE TEXT BY USING SKIMMING TECHNIQUE - Wahyuni, Tri; Bunau, Eusabinus; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research is on intended to answer the problem about to know how well the use of skimming technique improves students’ reading comprehension on descriptive text to the first semester of the tenth grade of SMA Negeri 2 Teluk Keramat in the academic year 2013/2014. In this research, Skimming technique is reading technique in which focused on improve the students reading comprehension on finding out the main idea, detail information, vocabulary and inference on descriptive text. This technique guided the students to comprehend the information of descriptive text about animals. This study used classroom action research method. The tools of data collection used reading test, observation checklist, and field note. On the first and second cycle the writer used picture, text and table as helping technique. From the result of measurement test, the data show that the students’ mean score on first cycle was 60.11. Then the second cycle the students’ mean score was 80.92. From the result of data analysis showed that students’ reading comprehension on descriptive text by using skimming technique improved. Keyword: Reading comprehension, descriptive text, and skimming technique. Abstrak: Penelitian ini bertujuan untuk menjawab masalah yaitu tentang untuk mengetahui bagaimana baiknya penggunaan skimming tekhnik dalam meningkatkan pemahaman membaca pada teks deskriptif untuk semester pertama pada kelas sepuluh di SMA Negeri 2 Teluk Keramat tahun ajaran 2013/2014. Dalam penelitian ini skimming tekhnik adalah tekhnik membaca yang mana berfokus dalam meningkatkan pemahaman membaca siswa dalam menemukan ide pokok, infornasi terperinci, tata bahasa dan menemukan kesimpulan pada teks deskriptif. Dengan teknik ini siswa dilatih untuk memahami isi bacaan deskripsi tentang hewan. Studi ini menggunakan metode penelitian tindakan kelas. Alat pengumpulan data menggunakan tes membaca, observasi centang dan halaman catatan. Dalam siklus pertama dan kedua penulis menggunakan gambar, teks dan table sebagai membantu tekhnik tersebut. Dari hasil tes penilaian, data menunjukkan bahwa nilai rata-rata siswa dalam siklus pertama adalah 60.11. Lalu siklus kedua rata-rata siswa adalah 80.92. dari hasil analisis data menunjukkan pemahaman membaca siswa pada teks desriptif menggunakan teknik skimming meningkat. Kata kunci : Pemahaman membaca, teks deskriptif, dan tekhnik skimming